PEMBENTUKAN PERATURAN DESA MENURUT UNDANG-UNDANG NOMOR 6 TAHUN 2014 PERSPEKTIF SIYASAH SYARIYYAH: Studi Desa Matajang Kecamatan Kahu Kabupaten Bone - Alda, Alda; Sastrawati, Nila (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2023)
In principle, village regulations are decisions of the village community which form the basis for administering village governance which aims to protect rights and obligations, regulate living together and maintain community order at and or the will of the community. This study aims to find out how village regulations are formed based on Law Number 6 of 2014 concerning Villages in Matajang Village, Kahu District, Bone Regency. The results of this study indicate that the Formation of Village Regulations in Matajang Village, Kahu District, Bone Regency is in practice the basis for regulating local community affairs as an effort to realize the aspirations and will of the community. However, in reality, the implementation of village regulations is only the responsibility of the village head and the Village Consultative Body (BPD) without involving community participation in all stages of drafting village regulations. In addition, the formation of law according to siyasa syariyyah must fulfill the elements of legality; ummah and shura.